2020
DOI: 10.13106/jafeb.2020.vol7.no11.147
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Economic Growth in Indonesia: A Dynamic Panel Model

Abstract: This study aims to analyze the effect of public spending, macroeconomic variables, and BPK opinion on economic growth. This study is motivated by the inequality of fiscal policy effectiveness between regions in Indonesia in influencing the economic growth of different regions, the ability of local governments to attract foreign investors, and the transparency of regional financial management in designing development programs to encourage regional economic growth. The analytical tool in this study is a dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This condition will reduce producers' productivity in producing various types of goods and services, thus having an impact on decreasing the absorption of labor. This decrease in labor absorption implies an increase in unemployment [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition will reduce producers' productivity in producing various types of goods and services, thus having an impact on decreasing the absorption of labor. This decrease in labor absorption implies an increase in unemployment [25].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the poverty research in Java was expanded by introducing several control variables consisting of the dependency ratio, education, and infrastructure for six provinces in Java in the period 2000-2017. The results showed that the dependency ratio and education significantly affected poverty, while infrastructure had a negative but not significant effect on poverty [25].…”
Section: Povertymentioning
confidence: 93%
“…An increase in economic growth is considered successful if the production of goods and services increases compared to the previous year or vice versa [2]. Economic growth is basically a long-term macro-economic problem that aims to increase real output (national income) and living standards (real income per capita) by covering 3 factors, a) capital; b) manpower; and c) production [3].…”
Section: Introductionmentioning
confidence: 99%